2006
DOI: 10.1042/bj20061178
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to alkyl-lysophospholipid-induced apoptosis due to downregulated sphingomyelin synthase 1 expression with consequent sphingomyelin- and cholesterol-deficiency in lipid rafts

Abstract: The ALP (alkyl-lysophospholipid) edelfosine (1-O-octadecyl-2-O-methyl-rac-glycero-3-phosphocholine; Et-18-OCH3) induces apoptosis in S49 mouse lymphoma cells. To this end, ALP is internalized by lipid raft-dependent endocytosis and inhibits phosphatidylcholine synthesis. A variant cell-line, S49AR, which is resistant to ALP, was shown previously to be unable to internalize ALP via this lipid raft pathway. The reason for this uptake failure is not understood. In the present study, we show that S49AR cells are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
3

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 43 publications
6
69
3
Order By: Relevance
“…33 Similar findings were reported in S49, a murine lymphoma cell line. 27 Considering the ability of FasL Sphingomyelin synthase 1 in FasL-induced apoptosis E Lafont et al to trigger a caspase-dependent inhibition of SMS activity in Jurkat cells, we hypothesized that SMS1 is a putative target of caspases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Similar findings were reported in S49, a murine lymphoma cell line. 27 Considering the ability of FasL Sphingomyelin synthase 1 in FasL-induced apoptosis E Lafont et al to trigger a caspase-dependent inhibition of SMS activity in Jurkat cells, we hypothesized that SMS1 is a putative target of caspases.…”
Section: Resultsmentioning
confidence: 99%
“…Murine lymphoma cells, completely deficient for SMS activity and lacking SM, were resistant toward alkyllysophosphatidylcholine. 27 Fas-mediated apoptosis was partly impaired in a murine leukemia cell line deficient in SMS, and overexpression of SMS1 restored full caspase activation and cell death. 28 Thus, a complete and sustained inhibition of SMS might alter membrane composition and properties through SM depletion and confer partial cell death resistance.…”
mentioning
confidence: 99%
“…Regarding the role of SMS in cell death, some studies reported that downregulation of SMS1 confers resistance to stress-induced apoptosis [40,41].…”
Section: Page 17 Of 43mentioning
confidence: 99%
“…Interestingly, expression of both SMS1 and SMS2 has been observed in all adherent cell lines analyzed so far (breast cancer MCF-7 cells, cervical cancer HeLa cells, hepatocellular carcinoma HepG2 cells, colon cancer CaCo 2 cells, human lung fibroblasts, human epithelial HEK-293 cells, mouse melanoma MEB4, mouse fibroblasts) whereas expression of SMS2 seems to be very low or absent in the majority of suspension cell lines (S49, WR19L/Fas, Ramos and U937 lymphoma cells, HL-60, Molt-4 and K562 leukemia cells and primary human B, T and monocytic cells) 58,62,[72][73][74] and Luberto, unpublished observations). Since SMS2 is in part localized at the plasma membrane, with its catalytic site oriented toward the outside of the cell and it is expressed mainly in adherent cells, it may serve a specialized function in cell-cell or cell to matrix interactions.…”
Section: Differential Expression Of Sms1 and Sms2mentioning
confidence: 99%
“…Subsequently, the involvement of SMS1 in the maintenance of raft homeostasis has been postulated in S49 mouse lymphoma cells. 73 A variant S49 cell line resistant to apoptosis induced by alkyl-lysophospholipids (ALP) turned out to be deficient in SM synthesis due to down-regulation of SMS1 expression. Since ALP appears to be internalized via raft-dependent endocytosis, it was suggested that SM depletion perturbs the internalization of ALP in the resistant S49 variant.…”
Section: Sms1 and Sms2 As Regulators Of Sm Homeostasis And Receptor-mmentioning
confidence: 99%